New Soliton Solutions of the (2+1)-Dimensional System Davey-Stewartson Equation - Ja'afar Mohamad Jawad, Anwar J; J. Abu-Al Shaeer, Mahmood; D. Petkovic, Marko (International Journal of Engineering and Technology, 2018)
In this paper, we derive several soliton solutions of the generalized Davey-Stewartson equation with the complex coefficients. First we use the travelling wave transformation to reduce the initial system to ODE. The equivalent ODE is then solved, giving several classes of solutions, depending on the values of the parameters. Finally, the Extended Tanh-Coth method and Modified simple equation method.Â Â